Analysis of Factors Affecting Rice Productivity in Five Area Based Paddy Farming Development Locations in Kutai Kartanegara Regency - Muh Yamin; Nur Hidayat; Herijanto Thamrin; M. Atta Bary; Mujibu Rahman; Karno Karno; Maman Setyawan; Mohammad Lutfi (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
This study analyzed the factors influencing rice productivity in five area-based paddy farming development locations in Kutai Kartanegara Regency. It highlighted the importance of agricultural machinery, irrigation, high-quality seeds, farming techniques, technical support, environmental factors, and effective harvest and post-harvest management. Statistical analysis revealed that most factors, with the exception of agricultural machinery, positively impacted yields. Productivity was constrained by significant challenges, including labor shortages due to workforce migration, water scarcity during dry periods, and reliance on second-generation hybrid seeds, which limited potential output. In addition, low soil pH and inconsistent harvesting practices contributed to pest and disease outbreaks, further diminishing yields. While farmers generally demonstrated sufficient farming skills, technical guidance remained crucial for improving productivity and morale. Addressing these issues required prioritizing improvements in irrigation systems, the adoption of superior seed varieties, soil quality enhancement through targeted fertilization, and integrated strategies to resolve labor shortages. These efforts were essential for achieving sustainable rice production and strengthening agricultural resilience in the region.